2007
DOI: 10.1002/mabi.200700023
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Copolymer Composition and Molecular Weight of Polyhydroxyalkanoate Generated by Saturation Mutagenesis of Aeromonas caviae PHA Synthase

Abstract: Amino acid substitutions at two residues downstream from the active-site histidine of polyhydroxyalkanoate (PHA) synthases are effective for changing the composition and the molecular weight of PHA. In this study, saturation mutagenesis at the position Ala505 was applied to PHA synthase (PhaCAc) from Aeromonas caviae to investigate the effects on the composition and the molecular weight of PHA synthesized in Ralstonia eutropha. The copolymer composition and molecular weight of PHA were varied by association wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 42 publications
(49 reference statements)
0
33
0
4
Order By: Relevance
“…Once beneficial mutations are found, subsequent saturation mutagenesis of these spots optimizes the beneficial effect (44). For example, in the PHA synthase of C. necator H16 (PhaC H16 ), a G4D mutation increases the protein expression level of PHA synthase (26).…”
mentioning
confidence: 99%
“…Once beneficial mutations are found, subsequent saturation mutagenesis of these spots optimizes the beneficial effect (44). For example, in the PHA synthase of C. necator H16 (PhaC H16 ), a G4D mutation increases the protein expression level of PHA synthase (26).…”
mentioning
confidence: 99%
“…15) Compared with PhaC Ac , PhaRC YB4 showed lower polymerization activity toward the 3HHx unit, but the dry cell weight of R. eutropha PHB À 4 expressing PhaRC YB4 (6.0 g/L) was twice as high as that expressing PhaC Ac (2.9 g/L) under the same culture conditions. 15) Furthermore, the PHA content of PhaRC YB4 -expressing strain (81 wt%) was also higher than that of the PhaC Ac -expressing strain (72 wt%). 15) Thus PhaRC YB4 was highly compatible with R. eutropha in terms of PHA production.…”
Section: )mentioning
confidence: 90%
“…15) Furthermore, the PHA content of PhaRC YB4 -expressing strain (81 wt%) was also higher than that of the PhaC Ac -expressing strain (72 wt%). 15) Thus PhaRC YB4 was highly compatible with R. eutropha in terms of PHA production.…”
Section: )mentioning
confidence: 92%
“…On the other hand, wild-type and mutant synthases of Pseudomonas sp. 61-3, which belongs to the class II PHA synthase, exhibited activity of less than 50 U/g toward the polymerization of 3HB-CoA (42). In a recent study, the enzymatic activities of the PHA synthase of Aeromonas caviae (PhaC Ac ) and some of its mutants, when expressed in C. necator PHB Ϫ 4 grown on fructose, were reported to be in the range of 18 to 249 U/g (41).…”
Section: Discussionmentioning
confidence: 99%
“…Efforts have been taken to alter and improve the properties of natural synthase enzymes via enzymatic evolution, with the goal of engineering a more active enzyme with broader substrate specificity (38). Several successful studies have reported the engineering of mutant synthases with up to 4-fold increased activity (1,26,42). Nevertheless, the search for a natural synthase with comparable properties still is widespread.…”
mentioning
confidence: 99%